Adolescent and Parent Experiences of Acceptance and Commitment Therapy for Pediatric Chronic Pain: An Interpretative Phenomenological Analysis - Marie Kanstrup; Abbie Jordan; Mike K. Kemani (MDPI AG, 2019)
Pediatric chronic pain is common and can be related to reduced functioning in many domains for the young person and their parents. Existing psychological treatments such as Acceptance and Commitment Therapy (ACT) have shown to be effective, but improvements are needed. Qualitative approaches can help improve our understanding of treatment processes and outcomes. The aim of the present qualitative interview study was to explore the lived experiences of young people and parents who had participated in ACT for pediatric chronic pain. Four young persons and four parents were interviewed, and data was analyzed using Interpretative Phenomenological Analysis (IPA). Three themes were generated, each comprising two subthemes: (1) ‘Warning system’, which included experiences from being offered this psychological intervention, and the alternative explanations provided for pain; (2) ‘Change and challenges’, which suggested the importance of the values-based work, and of individual adaptation; and (3) ’A common language’ in which the interaction with others and new ways to communicate around the pain experience were described. Findings highlight the importance of pain education, formulating and acting in line with personal values, and communication around the pain experience, as well as the need for developmental and individual adaptations of interventions.